Identification of Novel Sensitive and Reliable Serovar-Specific Targets for PCR Detection of Salmonella Serovars Hadar and Albany by Pan-Genome Analysis - Ye, Qinghua; Shang, Yuting; Chen, Moutong; Pang, Rui; Li, Fan; Xiang, Xinran; Wang, Chufang; Zhou, Baoqing; Zhang, Shuhong; Zhang, Jumei; Yang, Xiaojuan; Xue, Liang; et al. (Frontiers in Microbiology, 2021)
The accurate and rapid classification of Salmonella serovars is an essential focus for the identification of isolates involved in disease in humans and animals. The purpose of current research was to identify novel sensitive and reliable serovar-specific targets and to develope PCR method for Salmonella C2 serogroups (O:8 epitopes) in food samples to facilitate timely treatment. A total of 725 genomic sequences of 16 target serovars belonging to serogroup C2 and 150 genomic sequences of non-target serovars were analysed by pan-genome analysis. As a result, 4 and 3 specific genes were found for serovars Albany and Hadar, respectively. Primer sets for PCR targeting these serovar-specific genes were designed and evaluated based on their specificity; the results showed high specificity (100%). The sensitivity of the specific PCR was 2.8 × 101–103 CFU/mL and 2.3 × 10 3–10 4 CFU/mL for S. Albany and S. Hadar, respectively, and the detection limits were 1.04 × 10 3–10 4 CFU/g and 1.16 × 10 4–10 5 CFU/g in artificially contaminated raw pork samples. Furthermore, the potential functions of these serovar-specific genes were analysed; all of the genes were functionally unknown, except for one specific serovar Albany gene known to be a coded secreted protein and one specific gene for serovars Hadar and Albany that is a coded membrane protein. Thus, these findings demonstrate that pan-genome analysis is a precious method for mining new high-quality serovar-targets for PCR assays or other molecular methods that are highly sensitive and can be used for rapid detection of Salmonella serovars.